(untitled) - Stephen Barrett (New York, 2007)
This new edition of the most comprehensive text available in the field continues to provide a vast amount of information to enable consumers to make wise choices regarding health products and services. It offers a panoramic view of the health marketplace, while explaining the scientific methods that are essential for validating claims about how products and services affect health
Keywords: Consumer education; Health products; Medical care